Students' Difficulties In Writing Recount Text At The Eighth Grade Of Smp Murni 1 Surakarta In 2014/2015 Academic Year - Ratnasari, Annisa Dewi; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
This study aims at describing 1) the students' capability in writing recount text at the eighth grade of SMP Murni 1 Surakarta in 2014/2015 academic year, 2) the difficulties faced by the students in writing recount text at the eighth grade of SMP Murni 1 Surakarta in 2014/2015 academic year, and 3) teacher's solution to solve the problems faced by the students in writing recount text at the eighth grade of SMP Murni 1 Surakarta. This study uses content analysis. The object of this research is recount text written by the eighth grade students of SMP Murni 1 Surakarta in 2014/2015 academic year. The researcher gets the data of the research from students's work sheet in writing recount text, field note, script interview, teacher's material, and student's attendance list. And data sources of the research are event, informant and document.Mrthods of collecting data are observation, interview, and analyzing document. The researcher analyzing the data according to Anderson (1968) in Hughes (2003: 100). The students' capability in writing recount text at the eighth grade of SMP Murni 1 Surakarta is sufficient (61,8%). The difficulties faced by the eighth grade students of SMP Murni 1 Surakarta in writing recount text are: (1) the students are difficult in arranging generic structure completely, (2) the students are difficult in changing the tense, (3) the students are difficult in arranging grammatical sentence correctly, (4) the students have problem in choosing appropriate vocabulary, (5) the students are difficult in delivering their idea in writing recount text. The researcher gets solution to solve the problem faced by the eighth grade students of SMP Murni 1 Surakarta in writing recount text. There are: (1) giving explanantion repeatly to solve the students's problem in writing recount text (2) giving excercises to solve difficulties in grammar (3) guiding questions to solve the limited vocabulary (4) looking up at dictionary to differentiate past form of word and spelling (5) making draft/scheme to make the students understand about generic structure of recount text (6) teaching genre text in the morning to make students easier in developing their idea.